Palynological analysis of Dennstaedtiaceae taxa from the Paranaense Phytogeografic Province that produce monolete spores and its systematic implications (I): Blotiella lindeniana, Histiopteris incisa and Paesia glandulosa - Yañez, Agustina (2017)
The genera of Dennstaedtiaceae have sporophytes with very different morphological characteristics between each other, and this feature has made difficult the systematic circumscription of the family. This reason makes necessary the study of new characters that allow a better understanding of the relations within the group. The spore morphology and wall structure of Blotiella lindeniana, Histiopteris incisa and Paesia glandulosa from the Paranaense Phytogeographic Province were studied using light microscope, and scanning and transmission electron microscope. The exospore has two layers and, according to the species, the exospore surface bears pila, echinae, verrucae, bacula and tubercles. The perispore has two or three layers and its surface is psilate, baculate or rugulate. The variability found in the sculpture of the spores and their stratification and ultrastructure of perispore reflects the morphological differences observed in the sporophyte of the species studied. Additionally, while the stratification and ultrastructure of the exospore is shared by the Dennstaedtiaceae species, their ornamentation could be a character to distinguish species into the clade “hypolepidoide”. The finding of spores with similar characteristics in phylogenetically unrelated families allows us to suggest that palynological features do not have an evolutionary value to establish relationships between groups above the genus level.